Role of Ancillary Investigations in Medicolegal Autopsy to Establish the Cause of Death and Legal Implications - Arora, Arneet; Moirangthem, Sangita; Yadav, Jayanthi; Alikkal, Suhail; Gour, Aniket; Kaore, Navinchandra M. (Journal of Laboratory Physicians, 2023)
Sudden death in young females can have various causes and it is important to investigate the cause thoroughly. In cases with a vague history, postmortem ancillary investigation can also help to establish or rule out potential causes of death, such as underlying medical conditions or environmental factors. These investigations may include various laboratory tests, such as toxicology, histology, microbiology, and genetic analysis, as well as radiological imaging studies. This information not only helps in ascertaining the cause and manner of death but also helps in establishing the legal connotations in any medicolegal case.This is a case of a young woman allegedly 18 years brought for a medicolegal autopsy. She had been feeling unwell for a few days before her death, experiencing vomiting, weakness, and fatigue. Although no underlying disease was diagnosed, she was advised to take a pregnancy test. Fifteen days later, she died at home continuing to feel unwell. Upon autopsy, the young woman was found to be emaciated, and revealed a male fetus, of 4 to 5 months of gestational age, in her uterus. A radiological examination of bones conducted postmortem revealed that the age of woman was approximately 15 years old. Postmortem microbiology analysis revealed the presence of the bacteria Leuconostoc mesenteroides in a blood sample collected from the subclavian vein. The pathogenicity of this bacteria in the cause of death along with the role of ancillary investigation in the light of Indian criminal law and its challenges are being discussed.
Keywords: sudden death; young female; Leuconostoc mesenteroides; postmortem ancillary investigations; Indian POCSO Act; mandatory reporting